Data for "Insight into the Li/LiPON Interface at the Molecular Level: Interfacial Decomposition and Reconfiguration" - Wang, Kangli; Mollenhauer, Doreen; Justus Liebig University Giessen (My University, 2024)
This dataset contains the calculated structures involving the surface and interface for the publication: Kangli Wang, Jürgen Janek, Doreen Mollenhauer. "Insight into the Li/LiPON Interface at the Molecular Level: Interfacial Decomposition and Reconfiguration". Further information relevant to the reuse of the dataset can be found in the included readme file.
Keywords: ddc:540